Low red/far-red ratio can induce cytokinin degradation resulting in the inhibition of tillering in wheat (Triticum aestivum L.) - Lei, Kangqi; Tan, Qingwen; Zhu, Liqi; Xu, Libing; Yang, Shuke; Hu, Jinling; Gao, Lijun; Hou, Pan; Shao, Yuhang; Jiang, Dong; Cao, Weixing; Dai, Tingbo; et al. (Frontiers in Plant Science, 2022)
Shoot branching is inhibited by a low red/far-red ratio (R/FR). Prior studies have shown that the R/FR suppressed Arabidopsis thaliana branching by promotes bud abscisic acid (ABA) accumulation directly. Given that wheat tiller buds are wrapped in leaf sheaths and may not respond rapidly to a R/FR, systemic cytokinin (CTK) may be more critical. Here, systemic hormonal signals including indole-3-acetic acid (IAA), gibberellins (GA) and CTK and bud ABA signals in wheat were tested under a low R/FR. The results showed that a low R/FR reduced the percentage of tiller occurrence of tiller IV and the tiller number per plant. The low R/FR did not rapidly induced ABA accumulation in the tiller IV because of the protection of the leaf sheath and had little effect on IAA content and signaling in the tiller nodes. The significant change in the CTK levels was observed earlier than those of other hormone (ABA, IAA and GA) and exogenous cytokinin restored the CTK levels and tiller number per plant under low R/FR conditions. Further analysis revealed that the decrease in cytokinin levels was mainly associated with upregulation of cytokinin degradation genes (TaCKX5, TaCKX11) in tiller nodes. In addition, exposure to a decreased R/FR upregulated the expression of GA biosynthesis genes (TaGA20ox1, TaGA3ox2), resulting in elevated GA levels, which might further promote CTK degradation in tiller nodes and inhibit tillering. Therefore, our results provide evidence that the enhancement of cytokinin degradation is a novel mechanism underlying the wheat tillering response to a low R/FR.